Association between retinal sensitivity and the presence of quiescent choroidal neovascularization in pachychoroid diseases. - Rion Ozawa; Keiko Azuma; Yoko Nomura; Hiroshi Murata; Ryo Asaoka; Kohdai Kitamoto; Kohei Ueda; Tatsuya Inoue; Ryo Obata (PLoS ONE, 2022)
This study was conducted to examine retinal sensitivity (RS) in eyes with pachychoroid diseases and to analyze its association with the presence or absence of quiescent choroidal neovascularization (CNV), that can be protective against retinal dysfunction or atrophy in other macular diseases such as age-related macular degeneration. A total of 12 eyes of 12 patients aged ≥45 years having the characteristic findings of central serous chorioretinopathy but not presenting any exudative changes were included in this study. Choroidal vascular hyper permeability (CVH) was identified by indocyanine green angiography, and the presence or absence of CNV was evaluated by optical coherence tomography angiography. RS at 68 points was examined by microperimetry. The average RS corresponding to within and outside CVH was compared. The association between the difference in RS and the presence or absence of CNV was also analyzed. CNV was detected in six eyes (50%). In eyes without CNV, the RS within CVH was similar compared with that outside CVH. However, in eyes with CNV, the RS within CVH was significantly decreased compared with that outside CVH. Multiple regression analysis revealed the presence of CNV as an independent factor associated with RS. In eyes with pachychoroid diseases, RS decreased within the CVH area under the coexistence of nonexudative CNV.